A ring-shaped hemoprotein trimer thermodynamically controlled by the supramolecular heme–heme pocket interaction. Issue 11 (19th December 2018) - Oohora, Koji; Kajihara, Ryota; Fujimaki, Nishiki; Uchihashi, Takayuki; Hayashi, Takashi
Abstract : A thermodynamically controlled supramolecular assembling system of cytochrome b 562 predominantly forms a ring-shaped trimer in dilute solution. Abstract : Engineered cytochrome b 562, a small hemoprotein, with an externally-attached heme moiety via a moderately long linker at a suitable position predominantly forms a thermodynamically stable ring-shaped trimer in dilute solution. In an equilibrium between supramolecular polymerization and depolymerization, the ring-shaped trimer is kinetically trapped even in a concentrated solution.